The effect of a microbial consortium on spring barley growth and development in the Kemerovo region, Kuzbass - L. K. Asyakina; О. А. Isachkova; D. E. Kolpakova; Е. Е. Borodina; V. Yu. Boger; A. Yu. Prosekov (Зерновое хозяйство России)
The Kemerovo region is a region of extreme farming, and therefore requires the development of effective biological methods for improving productivity of cultivated plants adapted to these conditions. The purpose of the current work was to find plant growth-stimulating microorganisms associated with spring barley, as well as to form a microbial consortium on their basis and to conduct field trial. The objects of the study were spring barley seeds selected in the Kemerovo region, growth-stimulating microorganisms isolated from them, and consortia formed on their basis. During the study, there were isolated and tested 9 bacterial isolates for their ability to synthesize growth-stimulating substances (kinetin and indolyl-3-acetic acid). There were selected three strains with the best indicators SHv-2, SHv-5, SHv-6 for further studies. There has been found that the strains are capable of fixing nitrogen (SHv-2 – 800 µg/ml; SHv-5 – 210 µg/ml; SHv-6 – 840 µg/ml). There was also seen an ability to solubilize phosphates (SHv-2 – 2.53; SHv-5 – 1.25; SHv-6 – 3.33). The study of cultural, morphological and biochemical properties made it possible to identify such strains as SHv-2 – Pantoea allii; SHv-5 – Raoultella ornithinolytica; SHv-6 – Pantoea ananatis. Based on these microorganisms, there were made various variants of microbial consortia, which were also valued for their ability to produce growth-promoting substances and fix nitrogen. Consortium MC-7 composed with Pantoea allii, Raoultella ornithinolytica, Pantoea ananatis in a ratio of 1:1:3, respectively, showed maximum activity in terms of the studied parameters. Field trials of this consortium have shown that it successfully improves spring barley productivity. Despite abnormal weather conditions (lack of productive rains), there was an increase in the growth of crops treated by the consortium in comparison with control options. There have been established the most promising options for processing spring barley, options 3 and 4.